Dynamics of particle export on the Northwest Atlantic margin - Hwang, J.; Manganini, S. J.; Montlucon, D. B.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The Northwest Atlantic margin is characterized by high biological productivity in shelf and slope surface waters. In addition to carbon supply to underlying sediments, the persistent, intermediate depth nepheloid layers emanating from the continental shelves, and bottom nepheloid layers maintained by strong bottom currents associated with the southward flowing Deep Western Boundary Current (DWBC), provide conduits for export of organic carbon over the margin and/or to the interior ocean. As a part of a project to understand dynamics of particulate organic carbon (POC) cycling in this region, we examined the bulk and molecular properties of time-series sediment trap samples obtained at 968 m, 1976 m, and 2938 m depths from a bottom-tethered mooring on the New England slope (water depth, 2988 m). Frequent occurrences of higher fluxes in deep relative to shallower sediment traps and low Delta C-14 values of sinking POC together provide strong evidence for significant lateral transport of aged organic matter over the margin. Comparison of biogeochemical properties such as aluminum concentration and flux, and iron concentration between samples intercepted at different depths shows that particles collected by the deepest trap had more complex sources than the shallower ones. These data also suggest that at least two modes of lateral transport exist over the New England margin. Based on radiocarbon mass balance, about 30% (+/- 10%) of sinking POC in all sediment traps is estimated to be derived from lateral transport of resuspended sediment. A strong correlation between Delta C-14 values and aluminum concentrations suggests that the aged organic matter is associated with lithogenic particles. Our results suggest that lateral transport of organic matter, particularly that resulting from sediment resuspension, should be considered in addition to vertical supply of organic matter derived from primary production, in order to understand carbon cycling and export over continental margins. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1829; 490AT Times Cited:0 Cited References Count:61Y

Molecular and isotopic constraints on the sources of suspended particulate organic carbon on the northwestern Atlantic margin - Hwang, J.; Montlucon, D.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The abundance, carbon isotopic composition (Delta C-14 and delta C-13), and lipid biomarker (alkenones and saturated fatty acids) distributions of suspended particulate organic matter were investigated at three stations centered on the 2000, 3000, and 3500 m isobaths over the New England slope in order to assess particulate carbon sources and dynamics in this highly productive and energetic region. Transmissometry profiles reveal that particle abundances exhibit considerable fine structure, with several distinct layers of elevated suspended particulate matter concentration at intermediate water depths in addition to the presence of a thick bottom nepheloid layer at each station. Excluding surface water samples, the Delta C-14 values of particulate organic carbon (POC) indicated the presence of a pre-aged component in the suspended POC pool (Delta C-14
id: 774; 471WJ Times Cited:1 Cited References Count:73Y

Lateral organic carbon supply to the deep Canada Basin - Hwang, J.; Eglinton, T. I.; Krishfield, R. A.; Manganini, S. J.; Honjo, S. (Geophysical Research Letters, 2008)
Understanding the processes driving the carbon cycle in the Arctic Ocean is important for assessing the impacts of the predicted rapid and amplified climate change in this region. We analyzed settling particle samples intercepted by a time-series sediment trap deployed in the abyssal Canada Basin ( at 3067 m) in order to examine carbon export to the deep Arctic Ocean. Strikingly old radiocarbon ages ( apparent mean 14 C age = similar to 1900 years) of the organic carbon, abundant lithogenic material (similar to 80%), and mass flux variations temporally decoupled from the cycle of primary productivity in overlying surface waters together suggest that, unlike other ocean basins, the majority of the particulate organic carbon entering the deep Canada Basin is supplied from the surrounding margins.
id: 1830; 314KU Times Cited:7 Cited References Count:33Y

Incorporation of aged dissolved organic carbon (DOC) onto oceanic particulate organic carbon (POC): an experimental approach using carbon isotopes - Hwang, J.; Druffel, E. R. M.; Bauer, J. E. (Marine Chemistry, 2006)
id: 682

Penetration of anthropogenic carbon into organic particles of the deep ocean - Druffel, E. R. M.; Bauer, J. E.; Griffin, S.; Hwang, J. (Geophysical Research Letters, 2003)
[1] In the late 1980s, bomb C-14 was present in suspended particulate organic carbon (POC) from the North Central Pacific (NCP) and Sargasso Sea ( SS) throughout most of the water column, demonstrating that deep POC had exchanged with atmospheric CO2 in the past 30 years. Upon reoccupation of these sites in 1999 and 2000, respectively, we observed that the delta(13)C values of suspended POC were lower than those measured a decade earlier. This demonstrates that anthropogenic CO2 from fossil fuel and biomass burning has penetrated a major organic matter pool in the deep ocean. Delta(14)C measured in the suspended POC showed similar or higher values in the deep Sargasso Sea and decreased values in the deep NCP compared to those measured previously. We use a box model to show that the differences in the radiocarbon results are likely due to the presence of resuspended sediment that is laterally advected from the continental margin to the deep Sargasso Sea.
709dpTimes Cited:12 Cited References Count:29
Keywords: bomb radiocarbon; C-14; CO2; delta-c-13; MATTER; NORTH PACIFIC-OCEAN; SARGASSO SEA; Sediment; variability; water